Re-Islamization of the West African Ummah A Model for Tajdid? (American Journal of Islam and Society, 1987)
IntroductionHuman development, from the Islamic point of view, can be achieved onlyby following the footsteps of the Prophet (SAAS). The nearer one comes toimbibing the Message of the Quran, Sunnah, and Shari’ah in one’s life, themore humanly developed one becomes, because personal development in Islamis measured by one’s refinement in living this Message. The more refinedand developed are the persons in a community, the better will be their cultureand civilization.As long as Muslims continued moulding their life according to the Shari‘ah,their civilization in Medina, Baghdad, Andullis, Constantinople, and Delhiflourished. The decline and fall of Islamic civilization came when Muslimsstarted paying mere lip service to the formula of faith and departing fromthe spirit and purposes of the Shari‘ah. This was the unfortunate phenomenonthroughout the Muslim world. Fortunately, the rightly inspired people roseto bring back the erring Muslims to the path of the Shari’ah. This paper seeksto present an assessment of the dynamics used by a Mujaddid (a promoterof Tajdid or revival) of West Africa to re-Islamize a society that had sunkinto the abyss of confusion.Islam in West AfricaWest Africa, situated south of the Sahara desert, and which the Arabhistorians called Bilad al Sudan, has witnessed in the past, many Islamicempires, e.g., Ghana, Mali, Songhai, and Bornu, the last of which was theSokoto Caliphate. It emerged from the process of Tajdid (renewal or revival inaccordance with the Quran and Sunnah)’ which was started by Shehu(Shaikh) ‘Uthman Danfodio (1754-1817) in 1774, and which culminated in ...